Using Coronial Records to Provide Novel In-Depth Insights into Work-Related Fatal Injury - Rebbecca Lilley; Gabrielle Davie; Bronwen McNoe; Tim Driscoll (International Journal of Population Data Science, 2020)
Introduction New Zealand’s (NZ) workplace fatality record is very poor compared to similar OECD countries. The reasons for NZ’s poor performance are highly debated yet inadequately informed due to a lack of high quality fatality data. Due to incomplete official data on work fatalities in NZ, it is not currently possible to use routine official data collections to reliably report: i) who is fatally injured due to work activities, and ii) what groups should be prioritised for action.